Wpływ stylu kierowania na otwieranie kultury organizacyjnej - Zgrzywa-Ziemak, Anna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The author discusses how different leadership styles may affect the development of opened corporate culture. Rational leadership and democratic co-ordination were recognized as favourable, and autocratic co-ordination and charismatic leadership as unfavourable to influence culture openning. (according to Sikorski). The leadership styles of Goleman were also considered. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1184, s. 452-459